Frekuensi Makan, Asupan Energi Dan Protein Terhadap Status Gizi Pada Balita Di Puskesmas Minggir Sleman - Nendhi Wahyunia Utami; Dechoni Rahmawati (INVOLUSI: Jurnal Ilmu Kebidanan, 2020)
One of the health indicators assessed for its achievement in the Millennium Development Goals (MDGs) is the nutritional status of children under five. Apart from being a source of energy, food is also needed to replace damaged body cells and growth. Problems will arise if the food consumed exceeds the need. The excess energy will be stored in the body. If this situation occurs continuously, it will result in accumulation of fat in the body so that you are at risk of becoming overweight. Based on the data from previous research, there were 9.3% of children under five years old Puskesmas Minggir experiencing stunting problems. Nutritional problems experienced by children under five in the Minggir Community Health Center include stunting. The purpose of this study was to determine the effect of eating frequency, energy and protein intake on nutritional status in toddlers. This type of research is descriptive research. The population in this study were all toddlers who checked themselves at Minggir Health Center based on program evaluation records. The sampling technique in this study using purposive sampling The results of this study showed that the frequency of feeding had an effect on nutritional status by 94%, an increase in the frequency of eating by 55.2%, and an increase in z-score by 77.4%. Move aside Yogyakarta